2015
DOI: 10.1177/1934578x1501000841
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebral Distribution of α-Pinene and the Anxiolytic-like Effect in Mice following Inhaled Administration of Essential Oil from Chamaecyparis Obtusa

Abstract: The anxiolytic-like and stress reduction effects following inhaled administration of essential oil from Chamaecyparis obtusa (EOCO) have been reported. Volatile components are thought to produce these effects of EOCO by neurological transfer and pharmacological transfer. The regions of the brain in which inhaled compounds are found due to pharmacological transfer of EOCO are not known. This research was undertaken to clarify the relationship between the intracerebral distribution of -pinene, which is the main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…It is well reported in literature the anxiolytic activity of two isolated secondary metabolites: limonene [50,51] and α-pinene [16,52]. All these articles highlight action of compounds on the CNS evidencing the anxiolytic property from CLEO.…”
Section: Discussionmentioning
confidence: 94%
“…It is well reported in literature the anxiolytic activity of two isolated secondary metabolites: limonene [50,51] and α-pinene [16,52]. All these articles highlight action of compounds on the CNS evidencing the anxiolytic property from CLEO.…”
Section: Discussionmentioning
confidence: 94%
“…The main components of Compound Anshen essential oil are esters, alcohols, alkenes, alkyls and other compounds, with the highest content of D-limonene (24.07%), Linalool (21.98%), Linalyl acetate (15.37%), a-Pinene (5.39%) and α-Santalol (4.8%).D-limonene [42], Linalool [43], Linalyl acetate [44] and α-Santalol [45] have been reported to have central nervous sedative effect. In addition, D-limonene has anti-anxiety and soothing effects [46], Linalool has anti-anxiety and depression-like effects [47] and α-Pinene has anti-anxiety [48] and stress-relieving effects [49]. It is speculated that the sedative and hypnotic effect of Compound Anshen essential oil is related to its main chemical composition and activity.…”
Section: Discussionmentioning
confidence: 99%
“…There are different biological properties described to α-pinene, as well as essential oils containing this compound have been used to treat several diseases [153], although no affinity towards CBRs have been described [154]. Alpha-pinene has been extensively investigated in the last years for its medicinal properties that include sedative, hypnotic, and anxiolytic [152,155]. In this context, Yang and colleagues demonstrated that α-pinene interacts with GABA A /benzodiazepine receptors prolonging its synaptic transmission, significantly increasing the duration of non-rapid eye movement sleep (NREMS), and reducing sleep latency [151].…”
Section: Alpha (α)-And β-Pinenementioning
confidence: 99%